URBAN SUSTAINABILITY AND EXPANSION ORGANIZATION IN SOUTH MEDITERRANEAN - Al_Omari, Omar Mustafa (European Scientific Journal, ESJ, 2013)
In the Western context, notions of sustainable development often refer to the need to adjust existing economic models in order to maintain better balances between economic growth and social needs, while protecting local ecologies and reducing the negative impact of growth on the global environment. In the developing world, however, sustainable development takes on a rather different meaning. With the agendas of developing nations focused on addressing basic developmental challenges such as economic growth, water scarcity, food security, and health, other environmental and social aspects are considered secondary at best and, for the most part, a luxury that a developing nation cannot afford. During the past three decades, Major South Mediterranean city-regions have experienced considerable physical, economic and social transformations. Globalization and economic restructuring has resulted in these city-regions receiving the full impact of urbanization pressures. City-regions such as Dubai, Masqat, Beirut, Amman, and Cairo have advocate expansion organization approaches giving particular interest to urban sustainability in an attempt to ease these pressures. These approaches promote efforts to achieve the triple bottom line sustainability by balancing economic and social development, and environmental protection, and putting (more emphasis on compact and optimum development of urban forms). This paper evaluates the South Mediterranean cities and assesses their experiences in managing their urban forms whilst promoting sustainable patterns of urban development. The findings show that sustainable urban development initiatives employing a top down approach has yielded encouraging results in these case study city-regions. However the need for a more concerted effort towards the overall sustainability agenda still remains vital.